2022
DOI: 10.1371/journal.pone.0271831
|View full text |Cite
|
Sign up to set email alerts
|

Six groups of ground-dwelling arthropods show different diversity responses along elevational gradients in the Swiss Alps

Abstract: Elevational gradients along mountain slopes offer opportunities to study key factors shaping species diversity patterns. Several environmental factors change over short distances along the elevational gradient in predictable ways. However, different taxa respond to these factors differently resulting in various proposed models for biodiversity patterns along elevational transects. Using a multi-taxa approach, we investigated the effects of elevation, area, habitat and soil characteristics on species richness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…Elevational variations in diversity have been quantified previously for both spiders and insects, but the patterns have not been uniform among different studies. For instance, the taxonomic diversity of spiders has shown declines with elevation (Winkler et al, 2018), hyperbolic relationships with elevation (Gilgado et al, 2022), and no elevational variation (Dolson et al, 2020). Similar variation has been observed in how insect communities respond to elevational gradients (e.g., Despland et al, 2012; Winkler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Elevational variations in diversity have been quantified previously for both spiders and insects, but the patterns have not been uniform among different studies. For instance, the taxonomic diversity of spiders has shown declines with elevation (Winkler et al, 2018), hyperbolic relationships with elevation (Gilgado et al, 2022), and no elevational variation (Dolson et al, 2020). Similar variation has been observed in how insect communities respond to elevational gradients (e.g., Despland et al, 2012; Winkler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These results match the findings by Gilgado et al (2022) where soil pH affected the species composition of ants, beetles, and centipedes when these parameters were compared at different levels of elevation. However, this contrast with Pan et al (2018), where soil pH was invariable in influencing the species composition of ground-dwelling arthropods.…”
Section: )supporting
confidence: 89%
“…The results of previous studies showed that ant species richness decreased as the elevation increased [25,38,[55][56][57]. However, in the eight elevational transects of the central and northern Sichuan Plateau, this trend is not consistent.…”
Section: Discussionmentioning
confidence: 74%
“…Two main patterns of biodiversity along elevational gradients have been identified: (1) a monotonous decrease with elevation [25,26]; and (2) a unimodal pattern with maximum diversity at middle elevation [27]. Although there have been many studies describing elevational ant diversity patterns [28][29][30][31][32][33][34][35][36][37][38], a unanimous conclusion about patterns remains elusive. Therefore, further investigation is required in different regions, especially in previously unstudied areas.…”
Section: Introductionmentioning
confidence: 99%